Application of Taguchi methods in the optimization of cutting parameters for surface roughness in turning - Mohamad Naim, Yusoff (2008)
In this study, the Taguchi Method is used to find the optimal cutting parameters for surface roughness in turning operation.The orthogonal array,the signal-to-noise ratio, and analysis of variance are employed to study the performance characteristics in turning operations of AISI 1030 steel bars using TiN coated tools.Three cutting parameters namely,insert radius,feed rate,and depth of cut,are optimized with considerations of surface roughness.Experimental results are provided to illustrate the effectiveness of this approach.